PERTUMBUHAN AYAM KUB YANG DIBERI PAKAN MENGANDUNG FESES SAPI TERFERMENTASI (Growth of KUB Chickens Given Feed Containing Fermented Cattle Feces) - Ndetu, Isabela Ene; Mulyantini, Ni Gusti Ayu; Malelak, Gemini E M (Universitas Nusa Cendana, 2025)
Cattle feces can be used as poultry feed, but their utilization is limited due to their high crude fibre and low crude protein content. Therefore, innovation in the form of fermentation is needed, as it can break down crude fibre into more digestible compounds and increase crude protein. The purpose of this study was to examine the growth of KUB chickens fed with fermented cattle feces. This study used 100 DOC KUB chickens. The design used was a completely randomized design with 4 treatments and 5 replications. Four treatments observed were R0: commercial ration (control), R1: commercial ration 90% + 10% fermented cattle feces, R2: commercial ration 80% + 20% fermented cattle feces, R3: commercial ration 70% + 30% fermented cattle feces. The observed variables were body weight gain (PBB), ration consumption, ration conversion and carcass weight. The data obtained were analyzed using ANOVA and followed by Duncan’s test to determine, if there were significant differences between treatments. The results of this study indicate that the provision of fermented cattle feces at a level of 20-30% in KUB chicken rations reduces ration consumption, body weight growth, ration efficiency, carcass weight and carcass percentage (P < 0.05). Based on the results of the study, it can be concluded that the inclusion of fermented cattle feces in KUB chicken rations (up to 10%) provides good results for the growth of KUB chickens.